Long-term economic cycles and the hyperglobalization crisis - Erquizio Espinal, Alfredo (Posgrados de la División de Ciencias Económica Administrativas, 2023)
The world economy is in the downward phase of its fifth Kondratieff cycle (K5) marked by the global recessions called Great Recession 2009 and Great Contraction 2020. What is in question is when this phase will end and the upward phase of a sixth cycle will begin. Kondrateff (K6). Likewise, the Hyperglobalization that began in the mid-nineties, has entered into crisis in a time frame that coincides with the chronology of the ascending phase of the K5 (1992-2008) and in the current debate regarding the exit from the Hyperglobalization crisis. scenarios of reglobalization, slow globalization and deglobalization are ventured. Since the aforementioned Hyperglobalization was a process that accompanied the ascending phase of K5, the resolution of its crisis will mark the end of the descending phase of the K5 and the beginning of the ascending phase of K6. Here the recent bibliography on the matter is synthesized and discussed, to contribute to the reflection on the new coordinates to understand the current and future reconfiguration of the world and the processes of economic integration.